2018
DOI: 10.3389/fmicb.2018.02494
|View full text |Cite|
|
Sign up to set email alerts
|

Altered Gut Microbiota and Compositional Changes in Firmicutes and Proteobacteria in Mexican Undernourished and Obese Children

Abstract: Mexico is experiencing an epidemiological and nutritional transition period, and Mexican children are often affected by the double burden of malnutrition, which includes undernutrition (13.6% of children) and obesity (15.3%). The gut microbiome is a complex and metabolically active community of organisms that influences the host phenotype. Although previous studies have shown alterations in the gut microbiota in undernourished children, the affected bacterial communities remain unknown. The present study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
125
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 70 publications
15
125
0
2
Order By: Relevance
“…The gut microbiota may also contribute to weight loss. In our study, the taxonomic group which was most affected by the reduction of nutrient supply was Lachnospiraceae, which is a bacterial family known to have the highest energy-harvesting properties (59,60) . Studies demonstrated that a 20 % increase in Firmicutes (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…The gut microbiota may also contribute to weight loss. In our study, the taxonomic group which was most affected by the reduction of nutrient supply was Lachnospiraceae, which is a bacterial family known to have the highest energy-harvesting properties (59,60) . Studies demonstrated that a 20 % increase in Firmicutes (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…Contrary, some studies revealed a decrease in diversity in obese patients [27,28]. Regarding the Mexican children population, one study shows a higher diversity associated with obesity [29], and the other two studies showed no difference in diversity among obesity and normal-weight controls [30,31]. Thus, the role of bacterial richness and diversity in children obesity remains unclear, suggesting that more studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relative abundance of f-Lachnospiraceae was decreased by HFD, but increased by AFG. f-Lachnospiraceae has been reported to be associated with anti-inflammatory activity [18], host mucosal integrity [19], the consumption of energy and the level of leptin [20]. Fructan [21,22] and whole garlic [23] have been reported to increase the abundance of f-Lachnospiraceae, but alliin was found to decreased it [24].…”
Section: Discussionmentioning
confidence: 99%